Gratuitous overexpression of genes in Escherichia coli leads to growth inhibition and ribosome destruction. - Dong, H (1995)
We attempted to test the idea that the relative abundance of each individual tRNA isoacceptor in Escherichia coli can be altered by varying its cognate codon concentration. In order to change the overall codon composition of the messenger pool, we have expressed in E. coli lacZ with the aid of T7 RNA polymerase so that their respective gene products individually accounted for 30% of the total bacterial protein. Unexpectedly, the maximum expression of either test gene has no specific effect on the relative rates of synthesis of the tRNA species that we studied. Instead, we find that there is a cumulative breakdown of rRNAs, which results in a loss of ribosomes and protein synthetic capacity. After either of the test genes is maximally induced, there is a growing fraction of protein synthesis invested in beta-galactosidase or delta tufB that is matched by a comparable decrease of the fraction of normal protein synthesis. We have also observed enhanced accumulation of two heat shock proteins during overexpression. Finally, after several hours of overexpression of either test protein, the bacteria are no longer viable. These results are relevant to the practical problems of obtaining high expression levels for cloned proteins.